Activation of the Stt7/STN7 Kinase through Dynamic Interactions with the Cytochrome b 6 f Complex . Issue 1 (3rd March 2016) - Shapiguzov, Alexey; Chai, Xin; Fucile, Geoffrey; Longoni, Paolo; Zhang, Lixin; Rochaix, Jean-David
Abstract : The N-terminal domain of the Stt7/STN7 protein kinase is essential for its activity and interacts directly with the Rieske protein of the cytochrome b6 f complex. Abstract: Photosynthetic organisms have the ability to adapt to changes in light quality by readjusting the cross sections of the light-harvesting systems of photosystem II (PSII ) and photosystem I (PSI ). This process, called state transitions, maintains the redox poise of the photosynthetic electron transfer chain and ensures a high photosynthetic yield when light is limiting. It is mediated by the Stt7/STN7 protein kinase, which is activated through the cytochrome b  6   f complex upon reduction of the plastoquinone pool. Its probable major substrate, the light-harvesting complex of PSII, once phosphorylated, dissociates from PSII and docks to PSI, thereby restoring the balance of absorbed light excitation energy between the two photosystems. Although the kinase is known to be inactivated under high-light intensities, the molecular mechanisms governing its regulation remain unknown. In this study we monitored the redox state of a conserved and essential Cys pair of the Stt7/STN7 kinase and show that it forms a disulfide bridge. We could not detect any change in the redox state of these Cys during state transitions and high-light treatment. It is only after prolonged anaerobiosis that this disulfide bridge is reduced. It is likely to be mainly intramolecular, although kinase activation may involve a transient covalently linked kinase dimer with two intermolecular disulfide bonds. Using the yeast two-hybrid system, we have mapped one interaction site of the kinase on the Rieske protein of the cytochrome b  6   f complex.